Nulla dies sine linea (ani jeden dzień bez owocnej pracy) - Skrzypczak, Józef (Wydawnictwo Naukowe UAM w Poznaniu, 2003)
The article presents the profile of Dr. h.c. Prof. Kazimierz Denek, head of Dept, of General Didactics at Adam Mickiewicz University in Poznań. The publication corresponds with Professor’s seventieth birthday. His achievements in Polish science and research are unquestionable: over 1,200 publications including more than 30 monographs; hundreds of promoted Master theses and a few dozen promoted doctoral dissertations and postdoctoral theses; numerous reviews and super-reviews in professorial programs; membership in many distinguished editorial boards; as well as great contribution in popularization of tourism and educational aspects of touring (supported by his own tourist activity). All the above allows to place Prof. Denek among the most outstanding educators in Poland. Unlike the others, he combines so dynamically and consistently his research interests with educational activeness in the issue of upbringing through tourism and touring. The article comprises documentation of Professor’s achievements as well as their evaluation.
Nulla dies sine linea (not a single day without fruitful work)